STUDY OF PHYSICAL AND MECHANICAL PROPERTIES OF GRANULAR FEEDS DISTRIBUTED TO FISH - Fazliddin Kurbonov (Bright Mind Publishing, 2025)
In a period when fisheries are developing in the world and the demand for fish products is increasing, the use of energy and resource-saving technologies and equipment for fish feeding and feeding is taking one of the leading places. Considering that “around 180 million tons of fish and fish products are produced worldwide, of which 32 percent are raised in ponds” and that granulated feeds are mainly used for feeding them, improving the quality of granulated feed distribution, reducing labor costs and costs, in turn, requires the widespread introduction of high-quality, energy- and resource-saving feed distributors into practice.
Keywords: Granulometric composition, device, granular feeds, technological process, fish ponds, method.